The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11661-020-05926-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermetallic Microstructure on Degradation of Mg-5Nd Alloy

Abstract: The influence of intermetallic microstructure on the degradation of Mg-5Nd alloy with different heat treatments was investigated via immersion testing in DMEM + 10 pct FBS under cell culture conditions and subsequent microstructural characterizations. It was found that T4 heat-treated sample had the poorest corrosion resistance due to the lack of finely dispersed precipitates inside grains, continuous lamellar particles along grain boundaries and outer Ca-P layer, and to the formation of a loose corrosion prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Mg alloys generally have poor corrosion resistance due to the low electrochemical stability of the Mg matrix, the strong cathodic activity of the secondary phases present, refs. [10][11][12], and the limited stability of the MgO surface film in aqueous solutions [13][14][15]. The solid solution of yttrium (Y) decreases the electrochemical activity of the Mg matrix and stabilizes the surface through the formation of Y 2 O 3 [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Mg alloys generally have poor corrosion resistance due to the low electrochemical stability of the Mg matrix, the strong cathodic activity of the secondary phases present, refs. [10][11][12], and the limited stability of the MgO surface film in aqueous solutions [13][14][15]. The solid solution of yttrium (Y) decreases the electrochemical activity of the Mg matrix and stabilizes the surface through the formation of Y 2 O 3 [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The β -Mg 12 Nd is a metastable phase, and its amount increases with the Nd levels, based on the statistical results mentioned above. Other reports [ 18 , 44 , 45 ], however, indicated that the β e -Mg 41 Nd 5 phase could also be detected in the as-extruded Mg–Nd alloys and at high temperatures. Actually, the sequence and type of precipitation are affected by the alloy state, solidification condition, heat treatment process, etc.…”
Section: Resultsmentioning
confidence: 95%
“…Extensive efforts have been devoted to improving the corrosion resistance of Mg through microstructural and surface modifications [42]. The microstructural approach starts with fabricating high purity Mg or alloying it with various elements such as zinc (Zn) [43,44], calcium (Ca) [45], manganese (Mn) [46], lithium [47], or rare-earth elements [48][49][50]. Then the Mg is plastically deformed into desired geometries through extrusion, rolling, forging, or drawing.…”
Section: Introductionmentioning
confidence: 99%